Exploring the Green Agenda in Human Resource Management and Organizational Performance: A Systematic Literature Review - Jimoh, Adams Lukman (International Review of Management and Marketing, 2026)
This study gives a detailed review of literature on green human resource management and its connection to organizational performance. The increasing environmental issues and challenges concerning sustainability have promoted the ecological concerns incorporated by organizations in the way they are managed, making human resource management a major contributor of ecologically responsible organizational behavior. Even though more and more scholars are interested in the area, current studies on green HRM have been disjointed in terms of the conceptual definitions, theoretical backgrounds, and methods. This study will solve these shortcomings by presenting the systematic literature review that is controlled by the PRISMA 2020 in combination with bibliometric mapping via VOSviewer. A systematic search of the databases Scopus, Web of Science, and ScienceDirect found 315 records; it reached a final sample of 150 peer-reviewed articles published between 2000 and 2025. The results indicate that the practices of green HRM are usually conceptualized with the practices of green recruitment, environmental training, sustainability-oriented performance management, and employee eco-engagement. The empirical data show that the practices lead to the improvement of environmental performance, employee engagement, and possible financial gains. The review also determines the prevailing theoretical views and methodological tendencies that inform the field. The research provides a clear framework of the future research by reorganizing scattered knowledge and revealing research gaps that could be used in the future to inform other organizations that need to integrate sustainability principles in the human resource management models.